Medical Waste Generation of Community Health Centers (PUSKESMAS) In Magelang Regency, Indonesia (Applied Research in Science and Technology, 2021)
The majority of Magelang Regency’s society is registered as participants and actively uses the Indonesian National Health Insurance (JKN). This makes the active role of Community Health Centers as first level service that takes care of health problems. This has an impact on the amount of hazardous waste by the Community Health Centers activities and how to manage it. The study was carried out to identify and calculate hazardous waste generation in Community Health Centers. The study was conducted using a purposive sampling method by examining the Community Health Centers services (e.g., hospitalization and out-patient care) and analyzing medical waste generation based on SNI 19-3964-1994 standard. The study results indicate that the type of Community Health Centers has an impact on the daily generation and composition of hazardous waste. The composition of non-sharp infectious waste produced was as much as 82%, and that sharp infectious waste was 18% average from hospitalization and out-patient care. The potential for waste generated from Community Health Centers in Magelang Regency is as much as 33.66 kg per day. This needs to be reconciled with the increasing knowledge of health workers and sanitarians in handling this. The generation and composition of hazardous waste in Community Health Centers are influenced by several factors, including the type of Community Health Centers service, the number of patients and treatments provided, and the extent of laboratory services.